Atomic House (1953)
Caption with photograph reads: 'A view of a model of an atomic house designed by a California State Polytechnic College architecture student as a project for his senior thesis. The dome-shaped house is a structure capable of withstanding the fury of atomic shock waves.' See also us-pho_00001638